Community‐Based Palliative Care and Advance Care Planning Documentation: Evidence from a Multispecialty Group. Issue 2 (24th October 2017) - Tai‐Seale, Ming; Yang, Yan; Dillon, Ellis; Tapper, Sharon; Lai, Steve; Yu, Peter; Allore, Heather; Ritchie, Christine
Abstract : Background/Objectives: With the growing public demand for access to critical health data across care settings, it is essential that advance care planning (ACP) information be included in the electronic health record (EHR) so that multiple clinicians can access it and understand individuals' preferences for end‐of‐life care. Community‐based palliative care programs often incorporate ACP services. This study examined whether a community‐based palliative care program is associated with digitally extractable ACP documentation in the EHR. Design: Observational study using propensity score–weighted generalized estimation equations to examine patterns of digitally extractable ACP documentation. Setting: Palo Alto Medical Foundation (PAMF), a multispecialty ambulatory healthcare system in northern California. Participants: Individuals aged 65 and older with serious illnesses between January 1, 2013, and December 31, 2014 (N = 3, 444). Intervention: Community‐based palliative care program in PAMF. Measurements: Digitally extractable ACP in EHR. Results: We found that only 14% (n = 483) of individuals with serious illnesses had digitally extractable ACP in electronic health records. Of the 6% of individuals receiving palliative care, 65% had ACP, versus 11% of those not receiving palliative care. Study results showed a strong positive association between palliative care and ACP. Conclusion: Only a small percentage of individuals with serious illnesses had ACP documentation in the EHR. Individuals with serious illnesses infrequently used palliative care delivered by board‐certified palliative care specialists. Palliative care service use was associated with higher rates of ACP after controlling for organizational and individual characteristics using a propensity score weighting method. Scalable interventions targeted at non‐palliative care clinicians for universal access to ACP are needed.